2003
DOI: 10.1016/s1010-7940(02)00719-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pulmonary complications after pneumonectomy for lung cancer

Abstract: PC after pneumonectomy are associated with high mortality rates. Careful attention must be paid to patients with COPD and heart disease. Our results confirm the relevance of previous chest physiotherapy and the importance of the length of the surgical procedure to minimize the incidence of PC. The predicted pulmonary function (ppo-FEV1) may be useful to identify high risk patients for PC development and adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
1
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 21 publications
2
80
1
14
Order By: Relevance
“…The variety and incidence of postoperative complications after pneumonectomy have been examined in a number of studies, all of which reported that acute respiratory failure was the most common, [9][10][11] but, whether preoperative FEV 1 and FEV 1 /FVC, and predicted postoperative FEV 1 are independent risk factors remains unclear. 11,12) In our study, however, we excluded pneumonectomy from the analysis of postoperative complications since the number of pneumonectomy was too small to perform multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The variety and incidence of postoperative complications after pneumonectomy have been examined in a number of studies, all of which reported that acute respiratory failure was the most common, [9][10][11] but, whether preoperative FEV 1 and FEV 1 /FVC, and predicted postoperative FEV 1 are independent risk factors remains unclear. 11,12) In our study, however, we excluded pneumonectomy from the analysis of postoperative complications since the number of pneumonectomy was too small to perform multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the most common cause of cancer-related deaths worldwide (1). Surgical resection offers the best part in the treatment for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Poor pulmonary function parametersare strongly correlated with increased postoperative morbidity and mortality [1,[25][26][27]. In prospective studies, even with good pulmonary function the mortality rate for major lung resection was 2.7% -4% and morbidity rate was up to 41%.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the group with reduced lung capacity bordering on inoperability was the target group of our investigation. No single parameter for operative risk prediction exists, but there are several recommendations [4,25,34]. Severe reduction of FEV 1 was the main inclusion criterion for our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation